Towards species identification of the bathyal octopod Graneledone (Mollusca: Cephalopoda). Issue 8 (14th September 2017) - Voight, Janet R.; Kurth, Jessica A.
ABSTRACT: The number of skin warts has traditionally been cited as a means of separating species in the benthic octopod genus Graneledone, but species-level taxonomy has been problematic since the discovery of a second population. We investigated whether the distribution of skin warts can simply and reliably distinguish similar species by comparing North-east Pacific specimens of Graneledone and North-west Atlantic specimens of G. verrucosa . Two characters, the presence/absence of warts at the posterior tip of the dorsal mantle and the position of the most distal arm wart quantified by the arm sucker number, separate the species. The absence of warts from the distal arms, the third arm pair, and from the lateral web (Sector C) appears to separate these species from congeners based on literature information. Wart distribution may effectively distinguish species throughout the genus, accomplishing the necessary first step in furthering our knowledge of deep-sea biodiversity and reconstructing phylogenetic relationships.